Alternative labor market policies to increase economic self-sufficiency: mandating higher wages, subsidizing employment, and raising productivity - David Neumark (Institute for the Study of Labor (IZA), 2008)
The principal means by which individuals and families achieve economic self-sufficiency is through labor market earnings. As a consequence, it is natural for policy makers to look to interventions that increase the ability of individuals and families to achieve an adequate standard of living from participating in the labor market - a goal that has become even more prominent in the post-welfare reform era in the United States. This paper discusses some key policies that are used or can be used to increase economic self-sufficiency by increasing earnings, including mandating higher wages, subsidizing work, and increasing skill formation. Specifically, it reviews evidence on some of the main policies currently in place in the United States, including minimum and living wages, the Earned Income Tax Credit, wage subsidies, and school-to-work programs. Finally, it considers alternative policies that have recently been proposed.
Keywords: J18; 330; Minimum wages; living wages; earned income tax credit; wage subsidies; school-to-work; Arbeitsmarktpolitik; Niedrigeinkommen; Lebensstandard; Aktivierende Sozialhilfe; Mindestlohn; Lohnsubvention; Steuerbegünstigung; Berufseinstieg; Wirkungsanalyse; Soziale Mindestsicherung; USA